2018
DOI: 10.1074/jbc.ra118.003669
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal monoubiquitinated PEX5 interacts with the AAA ATPases PEX1 and PEX6 and is unfolded during its dislocation into the cytosol

Abstract: PEX1 and PEX6 are two members of the TPasesssociated with diverse cellular ctivities (AAA) family and the core components of the receptor export module of the peroxisomal matrix protein import machinery. Their role is to extract monoubiquitinated PEX5, the peroxisomal protein-shuttling receptor, from the peroxisomal membrane docking/translocation module (DTM), so that a new cycle of protein transportation can start. Recent data have shown that PEX1 and PEX6 form a heterohexameric complex that unfolds substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 92 publications
2
45
0
Order By: Relevance
“…1 , 2 ). Very recently, it was shown that the AAA–ATPase Pex1/Pex6 unfolds substrates by processive threading (Gardner et al 2018 ), and that monoubiquitinated Pex5, which interacts with the AAA–ATPases Pex1 and Pex6, is unfolded during its dislocation to the cytosol (Pedrosa et al 2018 ).…”
Section: Mysterious Machinery: New Proteins and Functions At The Peromentioning
confidence: 99%
“…1 , 2 ). Very recently, it was shown that the AAA–ATPase Pex1/Pex6 unfolds substrates by processive threading (Gardner et al 2018 ), and that monoubiquitinated Pex5, which interacts with the AAA–ATPases Pex1 and Pex6, is unfolded during its dislocation to the cytosol (Pedrosa et al 2018 ).…”
Section: Mysterious Machinery: New Proteins and Functions At The Peromentioning
confidence: 99%
“…First, DTM-embedded PEX5 is monoubiquitinated at a conserved cysteine residue [22,28]. Then, the REM extracts monoubiquitinated PEX5 into the cytosol in an ATP hydrolysis-dependent manner, a step that also results in the release of DTM-embedded PEX7 [26,[29][30][31][32]. Finally, monoubiquitinated PEX5 is rapidly deubiquitinated in the cytosol [18,20,33].…”
Section: Introductionmentioning
confidence: 99%
“…The need for ATP comes only at the next steps, when the machinery is reset, that is, when the receptor is extracted back into the cytosol thus freeing the DTM for another protein import event [55]. This involves (a) monoubiquitination of PEX5 at a conserved cysteine residue located near the N terminus of the protein by the RING peroxins of the DTM [56][57][58], (b) extraction of monoubiquitinated PEX5 into the cytosol by the ATP-dependent mechanoenzymes PEX1 and PEX6, a step that also releases PEX7 from the DTM [51,55,[59][60][61], and, finally, (c) the rapid deubiquitination of Ub-PEX5 in the cytosol [62][63][64].…”
Section: Introductionmentioning
confidence: 99%